STRATEGY FOR STRENGTHENING LOCAL CULTURE IN THE DEVELOPMENT OF WELLNESS TOURISM AT THE YOGA BARN, UBUD - Sutra Dewi, Luh Kartika; Relin D.E; I Wayan Wiwin (Ride: Journal of Cultural Tourism and Religious Studies, 2024)
Wellness tourism creates opportunities for health businesses and other businesses related to body, mental and soul health. Wellness tourism is part of illness prevention tourism which focuses on providing health and health services. Achieving wellness tourism strategies in development such as mental, spiritual, emotional, environmental, social and physical health. This research examines three problems, such as: 1) the vision - mission in developing wellness tourism in The Yoga Barn, Ubud, 2) application of local culture in developing wellness tourism in The Yoga Barn, Ubud, 3) strategies for strengthening local culture in developing wellness tourism in The Yoga Barn, Ubud. This problem will be dissected using Phenomenological Theory, which is a science oriented towards getting an explanation of visible reality. This research is a qualitative descriptive study with a wellness tourism concept. The research method in this research is located at The Yoga Barn, Ubud. The type and approach of this research is descriptive qualitative, sampling was carried out using purposive sampling including. The types of data in this research include qualitative data supported by interviews and quantitative data in the form of demographic data, while the data sources in this research include primary data through interviews and secondary data in the form of data on wellness tourism activities at The Yoga Barn, Ubud. Then, is the research instrument which includes interview guides, stationery and cellphones. Data collection techniques in this research include observation, interviews, literature study and document study. The determination and sampling technique uses accidental sampling technique. The data analysis techniques used include data reduction, data presentation and drawing conclusions and using STP (Segmenting, Targeting, Positioning) analysis. The research results obtained state that The Yoga Barn's vision is to shape the growth of The Yoga Barn, become a positive global influence, help find the desire for happiness, while its mission is to practice art and become a facilitator in non-medical healing. The application of local culture in developing wellness tourism is still using traditional healing techniques and the existing facilities and infrastructure are still based on local wisdom. The strategy to strengthen local culture is to develop identity, understand cultural philosophy and consistently apply local culture